PENGEMBANGAN PETUNJUK PRAKTIKUM BERBASIS SCIENCE, ENVIRONMENT, TECHNOLOGY AND SOCIETY MATERI PEMISAHAN CAMPURAN DI SMPN 24 PONTIANAK - Nurlianti, Nurlianti; Melati, Husna Amalya; Rasmawan, Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractResearch on the development of practical guideline based on science, environment, technology and society with the aim of adding teaching material products in the form of practical instructions. Practical guideline developed are appropriate to be used by determining the response of students and teachers to the product practicum instructions developer. the form of research used was a development research that adopted the Kemp device development model. The subject of this study was the seventh grade students with high, medium, and low ability as well as science teachers in junior high school 24 Pontianak. Data collection instruments ada used feasibility assessment, student respons questionaire and teacher respons questionaire. The results of data processing show that the practical guideline developed are suitable for use in learning. Results of assessment of content feasibility, presentation feasibility, language feasibility and graphical feasibility of 93%; 92.6%; 93.5% and 92.4% with very high criteria.The result of the student respons test and teacher respons to the total student achievement Products were 77,7% and 83,33% with high kriteria.Kata kunci: practical guideline, SETS based, mixed separation, feasibility